Ignored effects of phosphite (P+III) on the growth responses of three typical algae species. (1st February 2022) - Han, Chao; Ren, Jinghua; Wang, Baoying; Wang, Zhaode; Yin, Hongbin; Ke, Fan; Xu, Di; Zhang, Lei; Si, Xiaoxia; Shen, Qiushi
Abstract: Nowadays, the ubiquitous distribution and increasing abundance of P +III in waterbodies have caused serious concerns regarding its bioavailability and potential toxicity. However, our knowledge on these issues is relatively limited. We addressed previously unknown effects of P +III on three dominate algae species i.e. Microcystic aeruginosa ( M. aeruginosa ), Chlorella pyrenoidesa ( C. pyrenoidesa ) and Cyclotella. sp in eutrophic waterbodies in China. Remarkable declines in biomass, specific growth rate and Chl-a of algae cells treated with 0.01–0.7 mg/L P +III as sole or an alternative P source were observed, indicating P +III had an inhibitory effect on the algal growth. Besides, the intracellular enzyme activities e.g superoxide dismutase (SOD) and malondialdehyde (MDA) were significantly increased with P +III stress. M. aeruginosa and Cyclotella. sp cells seemed to be more sensitive to P +III toxicity than C. pyrenoidesa since cell membrane suffered more serious stress and destruction. These findings combined, it confirmed P +III could not be utilized as bioavailable P, but had certain toxicity to the tested algae. It indicated that the increased P +III abundance in eutrophic waterbodies would accelerate the algal cell death, which could have a positive effect against algal blooms. Our results provide new insights into assessing the ecological risks of P +III in aquatic environments. Graphical abstract: Image 1 Highlights: Responses of three dominant algae under various P +III regimes were investigated. P +III was unable to support any growth of three tested algae as a P source. M. aeruginosa and Cyclotella. sp were more sensitive to P +III toxicity. Increased P +III in waterbodies could have a positive effect against algal blooms.